2017
DOI: 10.1111/beer.12161
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable banking in Latin American developing countries: Leading to (mutual) prosperity

Abstract: This article examines multinational banks' (MNBs) approaches to corporate social responsibility (CSR) in developing countries' subsidiaries, particularly in Latin America. Building on in-depth case studies of two MNBs that are based in Europe and market leaders in Latin America, we analyze their CSR motivations and outcomes in host countries. We examine institutional environments by applying the national business system framework, and we suggest missing categories in its financial and educational dimensions. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 106 publications
1
45
0
1
Order By: Relevance
“…Similarly, Ferreira () observed that CSR activities influenced the financial performance of organizations. Relationship between CSR activities and mutual wellbeing of MNE and host market has been also widely examined in the EM context (Forcadell & Aracil, ). In this research, we identify the links between performance and sociopolitical activities based on material from secondary sources.…”
Section: Research Context and Methodologymentioning
confidence: 99%
“…Similarly, Ferreira () observed that CSR activities influenced the financial performance of organizations. Relationship between CSR activities and mutual wellbeing of MNE and host market has been also widely examined in the EM context (Forcadell & Aracil, ). In this research, we identify the links between performance and sociopolitical activities based on material from secondary sources.…”
Section: Research Context and Methodologymentioning
confidence: 99%
“…Scholars are increasingly using the NBS approach to understand the cross‐national variations in the firms’ behaviour in response to social issues (Forcadell & Aracil, ; Hofman, Moon, & Wu, ; Jamali & Neville, ; Kostova & Roth, ; Matten & Moon, ; Sahasranamam & Ball, ; Whitley ). The NBS approach posits that a given country's combinations of political, financial, educational, and labour systems, as well as its cultural systems, can affect the behaviours of the firms.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Similarly, it is suggested that the nature of the NBS in the country in which it operates can determine whether a firm displays the explicit or implicit form of CSR (see also Hyatt & Berente, ; Jamali & Neville, ). Other studies, however, raise some doubts about the relevance of the NBS framework in its current form in contexts other than developed and western countries (Amaeshi, Adegbite, & Rajwani, ; Amaeshi, Adegbite, Ogbechie, et al, ; Forcadell & Aracil, ; Hofman et al, ; Jamali & Karam, ; Jamali & Neville, ; Muthuri & Gilbert, ; Wood & Frynas, ).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Nevertheless, this concept is mainly oriented to its effects on the company (at a micro level), but it fails to explain the consequences of MNCs' activity on the economic development of the host country (at a macro level). The institutional necessity (IN) approach (Forcadell & Aracil, ) tries to overcome this research vacuum. This constitutes a particular type of IV associated to the wide idea of sustainable development, which involves pressing needs (Brundtland Report, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the CSRIN perspective considers MNCs as key entrepreneurial agents, evolving the traditional institutional approach that emphasizes the adaptation of the firm towards a focus on active agency (Cantwell, Dunning, & Lundan, ; Kostova, Roth, & Dacin, ; Meyer, ). Thus, CSRIN strategies imply a co‐evolution of the firm and its institutional environment, resulting in mutual prosperity (Forcadell & Aracil, ) for both the company and its emerging host country.…”
Section: Introductionmentioning
confidence: 99%